A reliability assessment approach for systems with heterogeneous component information. Issue Volume 30:Issues 4(2018) (2nd October 2018) - Xu, Jianyu; Yu, Dan; Hu, Qingpei; Xie, Min
ABSTRACT: Reliability assessment of complex systems is an important yet difficult task. The difficulty arises largely because of heterogeneous component-level data, for example, lifetime data, degradation data, component-level assessment results, and prior information. A method for reliability assessment is developed in this article for systems plagued by degradation and lifetime data. Our framework divides component-level information into two types. These two types are then combined using a systematic approach. This article describes the method along with some application examples that demonstrate the approach capable of overcoming several difficulties associated with conventional reliability assessment approaches.